Multi-channel medium access control protocols: review and comparison. Issue 1 (2nd January 2018) - Taneja, Kavita; Taneja, Harmunish; Kumar, Rohit
Abstract: Multi-Channel networks has been widely implemented and used in wired domain. The use of multi-channel provides increased network performance by efficiently utilizing the available bandwidth. The notion of multi-channels in wireless domain isn't as mature as their wired counterparts are. In past, many protocols have been invented using the concept of multi-channels in wireless domain. In this paper, all these major techniques has been presented, discussed and compared with respect to medium access control (MAC) methods of these techniques and protocols.